La guerre des mots dans la classe - Kovács, Máté (Linguistica (Ljubljana), 2018)
François Bégaudeau's The Class depicts the life of a class in a junior high school in Paris during a school year. This high school, which is attended by students from unprivileged social classes, is a theatre of conflicts between students and teachers. This study aims at analysing how words can become an instrument of war in the classroom. After a short overview of the linguistic diversity characterising education in France, our article studies excerpts of dialogues between students and their head teacher and explores the importance and function of the non-standard language represented in the book.
Keywords: analiza diskurza; Bégaudeau, François: Entre les murs; francoski romani; francoščina; nekonvencionalni jezik; osnovna šola